Development and Evaluation of Microcapsules Containing Combined Extracts of Bay, Cherry, and Green Betel Leaves as Natural Antioxidants - Pratama, Reza; Budiana, Wempi; Zaelani, Diki; Asnawi, Aiyi (Sciences of Pharmacy, 2025)
Bay leaf (Syzygium polyanthum), cherry leaf (Muntingia calabura), and green betel leaf (Piper betle) contain phenolic and flavonoid compounds with antioxidant potential, but their utilization is limited by physicochemical instability. This study aimed to develop microcapsules containing a combined extract of these three leaves and to evaluate their physicochemical properties and in vitro antioxidant activity as an initial formulation feasibility study. Each extract was prepared by maceration using 96% ethanol, yielding 11.42–15.86%, and combined in a 1:1:1 (w/w/w) ratio prior to microencapsulation. Microcapsules were produced using a fluidized bed dryer with lactose as the core material and polyvinyl alcohol (PVA) as the coating polymer. Physicochemical characterization included moisture content, flow rate, angle of repose, compressibility index, dissolution time, particle size, and surface morphology. Antioxidant activity was assessed using DPPH and CUPRAC assays, with IC₅₀ values calculated from triplicate measurements. The coating process increased mean particle size from 636.2 µm to 728.0 µm and prolonged dissolution time from 2.14 to 3.55 minutes, indicating coating layer formation. Among the individual extracts, cherry leaf extract showed the strongest antioxidant activity. The microcapsules exhibited antioxidant activity within the same order of magnitude as the combined extract under initial, non-stressed testing conditions. These results demonstrate the feasibility of formulating combined plant extracts into microcapsules with acceptable physical properties, while further stability and comparative studies are required to support antioxidant preservation and potential applications.